PROMOSI BUDAYA DAN PARIWISATA BERBASIS MEDIA DIGITAL: MENINGKATKAN KESADARAN KAUM MUDA TERHADAP WARISAN BUDAYA LOKAL - Yustus Sentus Halum; Ely Heldydiana Selamat; Theodisius Frederico Rondas; Yohanes Christian Mbohong; Yohanes Day Nagi (Unika Santu Paulus Ruteng, 2021)
As an effort to preserve cultural heritage which can also be an attraction in the tourism sector, social media is a digital media that is familiar to use among young people. The internet can have potential as a medium for community empowerment itself. Based on the thoughts, the implementing team for this Community Service activity has carried out community service activities with the title